The Relation Between Smoking and Knee Osteoarthritis in Sulaymaniyah Governorate/Iraq (Journal of Pharmaceutical Negative Results, 2022)
Background Osteoarthritis (OA) is a rather common, painful chronic degenerative disease that is considered a leading cause of disability worldwide. Knee joints are the commonest joints affected by OA. Smoking, as well, is a common social habit that is related to many chronic diseases such as cancer diabetes and cardiovascular diseases. The aim of this study was to find out the relationship between smoking and knee OA in Sulaymaniyah city /Kurdistan Iraq.Methods A cross-sectional study included 118 subjects with Knee OA who attended the Rheumatology center in Sulaymaniyah. After taking written consent, general and anthropometric data, inclusion and exclusion criteria and smoking history. We used the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) to evaluate the clinical features of OA, followed by a plain x-ray of both Knees to assess the Kellgren/Lawrence (KL) grades for each participant (only K&L grade≥2 was included). Chi-square, independent t-test and correlation were the statistical tests used to find out associated results.Results The smoking history of OA patients was commonly never smoking (57.6%), followed by current smoking (25.4%) and ex-smoking (16.9%). The radiograph showed (50.2%) of OA patients had K&L grade 2, (33.9%) of them had grade 3 and (15.9%) of them had grade 4. Never smoking was associated with greater WOMAC scores than ever-smoking (p 0.005, p =0.006, and p= 0.008). However, mean WOMAC scores were significantly higher among the female gender and older age(p=0.026) (R=0.352). On the other hand, no association was found between different smoking histories and K&L grades in both knees (p=0.066, p=0.15).Conclusion An inverse association was found between cigarette smoking and Knee OA regarding patients’ clinical symptoms using the WOMAC scoring index. Although this inverse association was not confirmed in the radiographic analysis. The effect of residual confounding might have contributed to this result. Further investigation of this relationship between smoking and knee OA is needed to determine the specific mechanism of this inverse association.